PENGUNGKAPAN PEMANFAATAN DANA CORPORATE SOCIAL RESPONSIBILITY UNTUK PENCAPAIAN MAQASHID SYARIAH PADA PT. PLN PERSERO - Efri Syamsul Bahri; Siti Humairoh; Ahmad Bisyri Syakur; Rianti Pratiwi (IAIN Batusangkar, 2020)
Research on disclosure of Corporate Social Responsibility (CSR) in relation to Maqashid Sharia in State-Owned Enterprises (BUMN) is still rarely conducted, even though the contribution of BUMN has been felt by the community for its benefits and Maslahah. This research aims to describe disclosure of the use of corporate CSR funds in achieving Maqashid Syariah. The research method uses qualitative and descriptive approaches. The technique of data collection are interviews, observation, and literature study. The data validity was done by triangulation. This research uses CSR program data in 2018. The results show that PT. PLN Persero uses CSR Funds contibuted to the achievement of Maqashid Syariah. CSR funds are allocated for five aspects of Maqashid Syariah, namely: protecting religion (hifdz inen), protecting life (hifdz nafs), protecting intelligence (hifdz aql), protecting children (hifdz nasl), and protecting property (hifdz maal). Based on this disclosure, the use of CSR funds for the achievement of the largest Sharia Maqashid is allocated for the aspect of protection of offspring (hifdz nasl). The allocation of CSR funds is IDR 34,168,729,546, or 26.93%. Meanwhile, the smallest amount of funds in the aspect of religious protection (hifdz in) is Rp. 18,046,879,497 or 14.22%. From this research, new insights are obtained about the contribution of CSR Funds to the achievement of Maqashi Syariah. Therefore, further research is needed to measure the effect of CSR funds on the achievement of Maqashid Syariah using other methods. In addition, further research can add data over several years and add the number of objects to several other state-owned companies.